THE POLLEX – INDEX COMPLEX AND THE KINETICS OF OPPOSITION - Kumar, Arunachalam (Journal of Health and Allied Sciences NU, 2012)
The term opposition is exclusive to human manual articulation. The origin and development of the opposable thumb was a milestone in evolutionary history of man. The transition from pongid, pithecoid to paranathropus and thereon to anthropoid apes was witness to the transformation of the apposable thumb to an opposable one. While a few marsupials, primates and prosimians can and do 'oppose' their digits (either of the forelimb or hind-limb) these articulations are non-classical and cannot be categorized as opposition. The shortness of the thumb in proportion to the size and length of the palm / foot handicaps performance of functionally efficient 'opposition' in most species (1).According to evolutionary biologists, one of the more singular factors elevating man as a higher mammal, as compared to any other, is the modification in the functional capability of the thumb. The human thumb stands alone in its talent to 'oppose'. Anatomically, 'opposition' implies the movement by which you can touch the tip of your thumb to the tips of other fingers of the same hand. No animal except the human kind has a truly opposable thumb(2)The biomechanics of opposition of the pollex with special reference to its preferred digit, the index is discussed in this paper, in the light of increasing stress and usage of these digits in modern man exposed to newer personal communication devices and technologies which demand dexterity and speed in manipulation of these specific joints for specialized functions
Keywords: pollex; opposition; retroposition; apposition; human evolution; physical anthropology